1984
DOI: 10.1007/bf02134255
|View full text |Cite
|
Sign up to set email alerts
|

Atopic cataract: Changes in the lens epithelium and subcapsular cortex

Abstract: Two lenses with atopic cataract, one from a 33-year-old man and one from a 50-year-old man, were examined by light and electron microscopy. The younger man had an anterior polar cataract and the older a subcapsular opacification of the entire subcapsular cortex. In the younger lens the epithelial cells in front of the anterior opacity were extremely large and contained an increased number of mitochondria. In the older lens epithelial cells were missing centrally. These morphological changes probably reflect a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…T h e focal epithelial degenerations has not previously been described in this or other types of cataract (Kobayashi & Suzuki 1975; Jensen & I a n -sen 1980; Fagerholm et al 1984). This seems to take place in an otherwise apparently healthy epithelium.…”
Section: Discussionmentioning
confidence: 57%
“…T h e focal epithelial degenerations has not previously been described in this or other types of cataract (Kobayashi & Suzuki 1975; Jensen & I a n -sen 1980; Fagerholm et al 1984). This seems to take place in an otherwise apparently healthy epithelium.…”
Section: Discussionmentioning
confidence: 57%
“…Histological analysis of fibrous opacification has shown lens epithelial cell flattening and layering and ECM production [7] . The same histological findings are observed in the skin of atopic dermatitis patients and the airway mucosa of bronchial asthma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic cataract is occasionally complicated by fibrous opacification [6] . Histological analysis of fibrous opacification shows the production of extracellular matrix (ECM) and flattening and layering of lens epithelial cells [7] . Similarly, in bronchial asthma, fibrosis due to ECM production and cellular flattening and layering are seen in the basal membrane in the airway, and these changes are referred to as airway remodeling [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it had been observed that Hrp60 is located in the mitochondrial membrane [65] and since a lens with atopic cataract had an increased amount of mitochondrias [66], it could be suggested that the increased energy produced by the mitochondria provoked an increased Hrp60 to protect the cells (Table 1). …”
Section: Heat Shock Proteins Involved In the Pathogenesis Of Oculamentioning
confidence: 99%